Korelasi Cakupan Imunisasi MR dan Suplementasi Vitamin A Terhadap Kejadian Campak di Jawa Timur - Kurnia Sari, Rike Sinta; Astutik, Erni (STIKES Yayasan RS.Dr.Soetomo, 2024)
Measles incident that occurred in East Java Province in 2022 is a case that has attracted quite a lot of attention. Some of the causes highlighted are the decline in immunization coverage and vitamin A supplementation since the COVID-19 pandemic. Therefore, in this study, a correlation analysis of MR immunization coverage and coverage of vitamin A supplementation for measles cases in East Java in 2022 was carried out using a correlation test. The data analyzed was obtained from the 2022 East Java Province Health Profile report with a population analysis unit. The analysis using the Spearman correlation test showed that the p-value between measles cases and MR1, MR 2 immunization coverage, and vitamin A supplementation was 0.039; 0.027; and 0.063. The correlation coefficient between MR1 and MR2 immunization against measles cases in East Java Province in 2022 is -0.289 and -0.316, respectively. Thus, it can be concluded that there is a correlation between measles cases and MR1 and MR2 immunization coverage in a negative direction. Still, there is no correlation between measles cases and vitamin A supplementation coverage in toddlers.